Childbirth Problems Were the Impact of Early Marriage on Buton Tribe Girls - Butona, Suryanti; Yusriani, Yusriani; Idris, Fairus Prihatin (Universitas Muslim Indonesia, 2023)
Until now, early marriage is still a phenomenon that is often found in Indonesian society, especially in rural areas or known as traditional society. Based on the preliminary results, it was found that two informants experienced the worst impact of early marriage when the baby died at birth and at the age of 1.5 years. The purpose of this study was to obtain information, study and analyze in depth the impact of early marriage on childbirth problems of Butonese teenage girls in Simi Village, Waisama District, South Buru Regency. This type of research is qualitative with a case study approach is the research method used. Qualitative research was used with the intention of examining the impact of early marriage on the health of Butonese teenage girls through in-depth interviews, observation and documentation during the study. The results of this study found that most of the ordinary informants in this study had performed the posuo ritual (pingitan), but most of the informants still felt the health effects of getting married at a young age. Of the 7 regular informants, most of them experienced health problems, namely labor problems, prolonged labor and infant health problems at birth, and death in infants and low birth weight (LBW) and not exclusive breastfeeding. The conclusion of this research is that early marriage has a negative impact on the problem of childbirth for young women of the Buton tribe, both adolescents who do the posuo ritual or those who do not.